Levels and diagnostic value of model-based insulin sensitivity in sepsis: A preliminary study - Shukeri W.F.W.M.; Mat-Nor M.B.; Jamaludin U.K.; Suhaimi F.; Razak N.N.A.; Ralib A.M. (Wolters Kluwer Medknow Publications, 2023)
antibiotic agent; corticosteroid; glucose; hypertensive factor; infusion fluid; inotropic agent; insulin; adult; Article; artificial ventilation; clinical article; cohort analysis; controlled study; diagnostic value; female; glucose blood level; hospital admission; human; inotropism; insulin dependent diabetes mellitus; insulin infusion; insulin sensitivity; intensive care unit; male; middle aged; non insulin dependent diabetes mellitus; predictive value; receiver operating characteristic; renal replacement therapy; retrospective study; sensitivity and specificity; sepsis